PENERAPAN HAK CIPTA SEBAGAI JAMINAN PIUTANG DALAM PERBANKAN - Fitriani Julfa (Truth de Journal, 2025)
Borrowing and lending an activity that often occurs in society. In the banking industry, you can find a credit section that provides loans. Banks have requirements for providing credit, one of which is to use collateral or guarantees. One of the guarantees applied to the banking world is fiduciary guarantees. In practice, banks are still unable to apply copyright as a guarantee for these activities. The method used is normative juridical by using a literature study approach and normative descriptive analysis to find out about copyright binding as a guarantee object. In addition, the research was complemented by interviews with banks in the city of Sukabumi. Data shows that there has been no implementation of copyright guarantees in Sukabumi City banks. The obstacles are found because there are still weaknesses in the law on copyright and the lack of socialization from the government, resulting in not all banks knowing that copyright can be used as an object of elegance.